Analysis of Educational and Social Values in The Tradisi Sedekah Lang in the Samawa Tribe Community of West Sumbawa - Budiman; Alif Ilman Mansyur (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2022)
One of the traditions from the field of agriculture that is often carried out by the people of West Sumbawa is "Sedekah Lang". "Sedekah" which means sharing/thanksgiving and "Lang" means a stretch of rice fields, this tradition is usually carried out before and after harvest. The hope is the reward of almsgiving that has been done as a form of gratitude to Allah Almighty. The purpose of this study is to determine the implementation, educational and social value of the Tradition of Alms Lang. This research uses a descriptive qualitative research method that analyzes the findings data and the data obtained in the field. The data collection methods used are observation, interview, and docmeation. Then the data found were analyzed using descriptive data analysis techniques. The results showed that the tradition of Sadekah Lang has been going on for a long time, since the time of the Sumbawa Kingdom and is still held until now and is a tradition that is held every year, the purpose is to get or ask for safety for the residents of Seminar Salit Village born and mentally and also as a form of expression of gratitude to the ruler of the universe who has given blessings in the form of good results from the harvest of community rice fields in that year. The educational and social values contained are religious values, tolerance, discipline, hard work, democracy, national spirit, love of the homeland, friendly and communicative, peace-loving, environmental care, responsibility, ingrained and dominant.